The bank guarantee in the Libyan development bank and their compatibility with Islamic Law: A jurisprudential applied study / Mohamed Alhassan Mohamed Hamed Alhodairy - Mohamed Alhassan, Mohamed Hamed Alhodairy (2018)
This study deals with examining the forms of bank guarantee contracts used in the Libyan Development Bank, and finding out the possible extent of its applicability and compliance with the Islamic Sharia law. The issue being studied is the nature of contraventions to the Islamic sharia perspective that may exist in the bank guarantees’ statements in the forms or in some parts thereof, which need to be corrected in order to comply with Islamic Sharia law. The study aims to show the conditions and rights that follow the personal and in-kind guarantee contracts, and how it is dealt with in the Libyan Development Bank, as well as disclosing the extent of compatibility of the application of the forms of bank guarantees’ statements in Libyan Development Bank with the Islamic Shariah law. The methodology adopted in this study is the analytical descriptive approach in order to analyze the jurisprudence issues related to bank guarantee contracts, so that they are applied to the banking applications. Also it was necessary to use the field survey, to study the contemporary state of implementation in the Libyan Development Bank of the banking guarantee forms through collecting data from secondary sources such as books, researches and scientific journals, as well as through referring to primary sources of forms’ models of the banking guarantees, banking regulations and decisions, and the questionnaire. One of the most important findings arrived at in the research is that documenting the contracts for bank guarantees is permissible in the Islamic sharia law, due to its importance in strengthening the obligation of the development contracts that are to be guaranteed. The forms of application of the banking guarantee contracts being implemented in the Libyan Development Bank in general were found to contain several violations of the sharia law in terms of having its documentation done ahead of assuring the collateral that is to be confirmed. In addition, there were other violations of the sharia law pertaining to the conditions requiring documenting especially for the personal guarantees contracts (banking guarantees) and in-kind guarantees (mortgages). All this made it necessary for the researcher to recommend the review of all the files related to the banking guarantee contracts in the Libyan Development Bank, and to take care of properly wording them legally and in accordance with the Islamic jurisprudence law in line with the sharia system of objectives.